2001
DOI: 10.1002/1097-0142(20010601)91:11<2096::aid-cncr1237>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

P21WAF1/CIP1 messenger RNA expression in hepatitis B, C virus-infected human hepatocellular carcinoma tissues

Abstract: BACKGROUND The primary objective of this study was to clarify the significance of p21WAF1/CIP1(p21) gene expression in the tumorgenicity of hepatitis B virus (HBV) and hepatitis C virus (HCV) infected human hepatocelluar carcinoma (HCC). METHODS The authors performed Northern blot hybridization to compare the p21 messenger (m) RNA expression levels among 16 HCC cases. They detected tissue HBVx mRNA (Northern blot) and plus‐ and minus‐strand HCV RNA (reverse transcription–polymerase chain reaction) in liver tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…The activation of p21 WAF1 induced by HDAC inhibitors results in the growth arrest by induction of G 1 arrest in several malignant cell lines [26,27]. Kobayashi et al documented the association between decreased expression levels of p21 WAF1 and hepatocarcinogenesis [28]. Both CYR61 and CTGF belong to CYR61/CTGF/ nephroblastoma-overexpressed family and affect extracellular matrix signaling [29].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of p21 WAF1 induced by HDAC inhibitors results in the growth arrest by induction of G 1 arrest in several malignant cell lines [26,27]. Kobayashi et al documented the association between decreased expression levels of p21 WAF1 and hepatocarcinogenesis [28]. Both CYR61 and CTGF belong to CYR61/CTGF/ nephroblastoma-overexpressed family and affect extracellular matrix signaling [29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in mice, depletion of p21 leads to a continuous proliferation of severely injured hepatocytes and rapid tumor development [91]. In lines with this, p21/Waf1 expression levels in the cancerous tissues appear to be significantly reduced compared to those in the noncancerous tissues [224, 225]. Furthermore, the histological negativity for p21/Waf1 serves as a negative prognostic factor for the survival of patients with HCC after resection [226], although a contrary finding has also been reported [227].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Kobayashi et al . [43] reported that p21 mRNA expression in normal tissues is significantly higher in HCV-positive cases compared to HBV-positive cases. These data supports our findings that p21 protein expression was affected not only by fibrosis but also hepatitis virus type.…”
Section: Discussionmentioning
confidence: 99%